Crystal methamphetamine use and bacterial sexually transmitted infections (STIs) among gay, bisexual and other sexual minority men in Canada. (1st January 2023) - Hart, Trevor A.; Noor, Syed W.; Tavangar, Farideh; Berlin, Graham W.; Skakoon-Sparling, Shayna; Tan, Darrell H.S.; Lambert, Gilles; Grace, Daniel; Jollimore, Jody; Sang, Jordan M.; Kirschbaum, Allison L.; Kanji, Rahim; et al.
Abstract: Objective: While crystal methamphetamine use by gay, bisexual, and other men who have sex with men (GBM) is associated with increased risk for sexually transmitted infection (STI) transmission, less is understood about the causal pathways between crystal methamphetamine use and STIs. We examined whether the association between greater crystal methamphetamine risk and prevalent bacterial STI diagnosis among GBM was mediated by two types of attitudinal variables: attitudes toward condoms, and sexual escape motives, defined as the use of substances to escape self-awareness during sex, and by sexual behaviors. Methods: We used computer-assisted self-interview questionnaires from 2449 sexually active GBM (18% living with HIV; median age = 33, interquartile range, 27–45) recruited via respondent-driven sampling in Vancouver, Toronto, and Montreal, Canada. Using the baseline data from the Engage cohort study, we fit a series of structural mediation models of the associations between greater crystal methamphetamine risk and bacterial STI (syphilis, gonorrhea, and chlamydia) diagnosis. We estimated indirect paths from greater crystal methamphetamine risk, attitudes toward condoms, sexual escape motives, and sexual risk behaviors, adjusting for self-reported demographic variables. Results: In the mediated model, the direct association between greater crystal methamphetamine risk and bacterial STI diagnosis was non-significant; however, five indirect paths were significant. Greater crystal methamphetamine risk was associated with bacterial STIs via condom use attitudes and escape motives, which in turn were associated with number of male anal sex partners, condomless anal sex, and oral sex. Discussion: Public health and counselling interventions for GBM who use crystal methamphetamine and who are at higher risk for STIs should target evidence-based causal paths that consider sexual attitudes and sexual practices. Highlights: Crystal methamphetamine (CM) risk is associated with STIs in sexual minority men (SMM). Indirect paths from CM risk to STIs via attitudinal variables and sexual behaviors. Targeted psychosocial STI prevention interventions are needed for SMM who use CM.